‘Everybody’s doing it’: on the persistence of bad social norms - Smerdon, David; Offerman, Theo; Gneezy, Uri (Experimental economics : a journal of the Economic Science Association, 2020)
We investigate how information about the preferences of others affects the persistence of ‘bad’ social norms. One view is that bad norms thrive even when people are informed of the preferences of others, since the bad norm is an equilibrium of a coordination game. The other view is based on pluralistic ignorance, in which uncertainty about others’ preferences is crucial. In an experiment, we find clear support for the pluralistic ignorance perspective . In addition, the strength of social interactions is important for a bad norm to persist. These findings help in understanding the causes of such bad norms, and in designing interventions to change them.